2000
DOI: 10.1080/11250000009356371
|View full text |Cite
|
Sign up to set email alerts
|

Elemental composition of the lichen Umbilicaria decussata

Abstract: Total concentrations of major and trace elements were determined in thalli of the epilithic lichen Umbilicaria decussata from 37 habitats in Victoria Land (continental Antarctica). Average concentrations of Pb, Cu, Zn, Cr, Mn and Fe were among the lowest ever reported for lichens of genus Umbilicaria. On the contrary, Cd and Hg concentrations fell within the same range or were higher than those usually measured in samples from remote areas of the southern and northern hemispheres. No impact of local or remote … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…This indicates that the contents of Pb and Cu in the thalli of U. aprina and U. decussata were lower than in the same species sampled near Maitri Station in the Schirmacher Oasis (Upreti & Pandev 1994). According to our data, the levels of the studied elements in U. decussata thalli were within the range reported for this species from Victoria Land in Continental Antarctica (Bargagli et al 2000).…”
Section: Discussionsupporting
confidence: 90%
“…This indicates that the contents of Pb and Cu in the thalli of U. aprina and U. decussata were lower than in the same species sampled near Maitri Station in the Schirmacher Oasis (Upreti & Pandev 1994). According to our data, the levels of the studied elements in U. decussata thalli were within the range reported for this species from Victoria Land in Continental Antarctica (Bargagli et al 2000).…”
Section: Discussionsupporting
confidence: 90%
“…Based on pH of samples, soils analyzed in this study were moderately acidic and slightly acidic (Bačkor and Fahselt 2004). Baseline concentrations of Cu, Cd, and Ni for both lichen species used in present study were much higher than those for lichens from some unpolluted or low polluted areas through the world, e.g., NW Territories, Canada (Chiarenzelli et al 1997), Antarctica (Bargagli et al 2000), or Greenland (Riget et al 2000). As the study site is a part of a border of Protected Landscape Area-Poľana, without recent industrial activity and considerable air pollution (confirmed by the presence of air pollution sensitive epiphytic lichens, including members of genus Usnea, Bačkor, unpublished data), substrate is the main source of metals for lichens, which are known to entrap particles from their substrate (Loppi et al 1999;Bergamaschi et al 2007).…”
Section: Discussionmentioning
confidence: 89%
“…Varueal Peak was a sampling site with highest Cu concentration and Lions Ramp with Cr and Ni. Median values of heavy metal concentration in lichen and moss samples from King George Island can be compared with values from Norway (Steinnes 2005 ; Barandovski et al 2006 ), reference plant model (Markert 1991 ), and literature data for Antarctic region (Bargagli et al 1999 ; Bargagli et al 2000 ; Gonzáles et al 2002 ; Smykla et al 2005 ; Lim et al 2009 ; Osyczka et al 2007 ; Zvěřina et al 2014 ; Bubach et al 2016 ) (Tables 6 and 7 ).…”
Section: Resultsmentioning
confidence: 99%